ISLAMIC SECURITIES CROWDFUNDING RESEARCH: A BIBLIOMETRIC ANALYSIS - Tafitri, Ulviya; Ulviya Tafitri; Aniva Nur Fadhilah; Muhammad Syafii Antonio (Universitas Airlangga, 2023)
The number of publications concentrating on Islamic Fintech and Securities Crowdfunding has significantly increased in recent years, especially from 2017 to 2023. Through bibliometric analyses using Dimension.ai, a dependable platform for accessing registered titles and abstracts, this growing interest has been thoroughly investigated. This investigation's main goal is to identify common topics and writing styles among the authors in this sector. The most recent information for this analysis was obtained by using the search term